Children's Environmental Health in Thailand: Past, Present, and Future - Ratchaneewan Sinitkul; Chathaya Wongrathanandha; Somkiat Sirirattanapruk; Adisak Plitponkarnpim; Richard J. Maude; Emma L. Marczylo (Ubiquity Press, 2018)
Background: There is increasing evidence of a link between environmental pollution and preventable diseases in developing countries, including Thailand. Economic development has generated several types of pollution that can affect population health. While these environmental health effects can be observed throughout life, pregnant women and children represent particularly vulnerable and sensitive groups. Methods: The published epidemiological literature investigating environmental chemical exposure in Thai children was reviewed, highlighting those that investigated associations between exposure and subsequent health outcomes. Results: The majority of the Thai epidemiological studies on environmental health in children were cross-sectional in design, with some demonstrating associations between exposure and outcome. The three main types of chemical exposure in Thai children were pesticides, heavy metals, and air pollution, which resulted from agricultural activities in countryside areas, industrial zones (both registered and unregistered establishments), mining, and traffic in inner cities. Major health outcomes included detrimental effects on cognitive function and cancer risk. Pesticide exposure was focused on, but not limited to, agricultural areas. The success of the Thai environmental policy to introduce lead-free petrol can be demonstrated by the decline of mean blood lead levels in children, particularly in urban areas. However, unregistered lead-related factories and smelters act as hidden sources. In addition, there is increasing concern, but little acknowledgement, about the effects of chronic arsenic exposure related to mining. Lastly, air pollution remains a problem in both dense city populations due to traffic and in rural areas due to contamination of indoor air and house dust with heavy metals, endotoxins and other allergens. Conclusions: The increasing number of published articles demonstrates an improved awareness of children's environmental health in Thailand. Chemical hazards, including the improper use of pesticides, environmental contamination with heavy metals (lead and arsenic), and air pollution in inner cities and indoor air, continue to be growing issues.